Stimulatory Effects of Acibenzolar-S-Methyl on Chlorogenic Acids Biosynthesis in Centella asiatica Cells - Ncube, Efficient N.; Steenkamp, Paul A.; Madala, Ntakadzeni E.; Dubery, Ian A. (Frontiers in Plant Science, 2016)
Centella asiatica is a perennial herb that grows in tropical regions with numerous medicinal properties, mostly attributed to the presence of pentacyclic triterpenoids. Interestingly, this plant also possess a significant amount of phenylpropanoid-derived chlorogenic acids (CGAs) that have recently been reported to confer neuroprotective properties. In a biotechnological attempt to increase the biosynthesis of CGA-derivatives in cultured Centella cells, acibenzolar-S-methyl was applied as a xenobiotic inducer in combination with quinic acid and shikimic acid as precursor molecules. Applying a semi-targeted metabolomics-based approach, time and concentration studies were undertaken to evaluate the effect of the manipulation on cellular metabolism leading to CGA production. Phytochemical extracts were prepared using methanol and analysed using a UHPLC-qTOF-MS platform. Data was processed and analysed using multivariate data models. A total of four CGA-derivatives, annotated as trans-5-feruloylquinic acid, 3,5 di-caffeoylquinic acid, 3,5-O-dicaffeoyl-4-O-malonylquinic acid (irbic acid) and 3-caffeoyl, 5-feruloylquinic acid, were found to be upregulated by the acibenzolar-S-methyl treatment. To the best of our knowledge, this is the first report on the induction of CGA derivatives in this species. Contrary to expectations, the precursor molecules had very little effects on the levels of the CGAs. However, a total of 16 metabolites, including CGA derivatives, were up-regulated by precursor treatment. Therefore, this study shows potential to biotechnologically manipulate C. asiatica cells to increase the production of these health beneficial CGAs.